ANALISIS BERBAGAI FAKTOR MAKRO EKONOMI YANG MEMPENGARUHI MANAJEMEN INDUSTRI ASURANSI KERUGIAN DI SEKTOR PERMINYAKAN - RUSDY WAHID (Media Bisnis, 2014)
Insurance undertakings become increasingly important role, because of its business activities in addition to providing protection to the community is also a deposit-taking institution that is sourced from premium revenue of the society in which these funds can be invested in productive sectors and safe as well as expected .industri this insurance can be more enhance the growth of gross domestic product (GDP). The development of the insurance industry in Indonesia can not be separated from economic and technological developments in human life. The more limited sources of human needs in an effort to increase its prosperity then grew human effort to utilize the resources that exist and attempt to secure either on themselves or their families and possessions of other events that may cause harm or cause disorder in achieving goals their life.